Analisis Neraca Massa Pada Pembuatan Serbuk Pewarna Alami Daun Sawi (Brassica rapa var. parachinensis L.) - Diana Ermawati; Andi Eko Wiyono (JOFE : Journal of Food Engineering, 2022)
Dyes made from natural ingredients sourced from animals and plants are used as food coloring. One of the natural green dyes is obtained from leaves that contain chlorophyll. One of the leaves that can be used as a dye is mustard greens because it contains chlorophyll. The purpose of this study was to analyze the mass balance in the process of making mustard leaf (Brassica rapa var. parachinensis L.). This research was conducted using laboratory experimental methods. The production of natural dye powder for mustard leaves is carriec out by means of material preparation,washing, blanching, extraction, addition of MgCO3 powder making and size reduction. The process ofmaking mustard leaf natural dye using mustard leaf 100 g, MgCO3 0,14 g, Tween 80 3,5014 g, and maltodextrin 35,014 g result in 33,8 g of dye powder. The mass balance of the process of making mustard leaf natural dye produces a final yield of 24,40%, the efficiency of the process in the powder making process is 0,087 (100%) with the highest mass loss in the blanching of 1.032 g.